Identification of Potentially Inappropriate Medications (PIMs) by Beers Criteria in Geriatric Patients at RSA UGM Yogyakarta - Ejaz, Sundas Ejaz; Rahmawati, Fita; Ikawati, Zullies (Majalah Farmaseutik, 2023)
PIM (Potentially Inappropriate Medications) is one of the primary concerns leading to adverse health outcomes, higher risk of Adverse Drug Reactions (ADEs), decreased therapeutic effects, hospitalization, and unnecessary healthcare costs in the geriatric population. Therefore, this study aimed to determine the prevalence PIMs, and to identify the most common PIMs prescribed to hospitalized geriatric patients admitted at RSA UGM, Yogyakarta based on Beers Criteria 2019. A cross sectional study using electronic medical records data was conducted in geriatric patients aged >60 years admitted to the internal medicine ward. PIMs were identified using the Beers criteria 2019. Descriptive statistics were used to describe patient and drug characteristics. Total 70 geriatric patients met the inclusion criteria. The results revealed that the geriatric patients who received PIM were male (65.71%), in the age group of 60-65 years (51.42%), had comorbidities and polypharmacy between 5-9 (48.5%) and 61.42% respectively. The overall prevalence of PIMs was 77.1%, followed by prevalence of PIMs to be used with caution (70 percent), and PIMs avoided in geriatric patients (62.8%). The most commonly prescribed PIMs were diuretics (48.5%) and sliding scale insulin (24.2%). A high prevalence of PIMs was found in this study, which is alarming. The prescription of PIMs can be overcome by encouraging strategies, such as close monitoring of the patient's condition for potential ADEs, gender and pharmacokinetic/pharmacodynamic consideration when prescribing drug therapy to geriatric patients.